FAKTOR YANG MEMPENGARUHI MOTIVASI BELAJAR SISWA PEMBELAJARAN SENI BUDAYA SUB SENI RUPA - Eda Alisa, Dr. Ramalis Hakim, M. Pd, Drs. Suib Awrus, M. Pd (Serupa The Journal of Art Education, 2013)
The purposes of research is to know intern factor and exstern factor that to influence the spint of student study in learning process visual art sub study visual art. The subject of research is kualitatif research with descriptif. The technique to find database is observation, interview, ang angket kuisoner. Research of find this coold resume on observation result, interview, and angket kuisoner, intern factor study is very well degree, can saw on behaviour, seriously, and activation students, then exstern factor students too degree well, well from social or then non social students. Keyword : Motivation, Intern Factor, Extern Factor.